Discourse on the Best Interpretation Model: A Critical Review of Traditional Exegesis Products in the Early Era - Mahdi Afandi; Abd. Kholid; Mursyid, Achmad Yafik (QOF, 2023)
In addition to interpreting the Qur'an through rational reasoning (ra'yi), scholars also employ an interpretive approach based on narrations, known as the bi al-ma’thūr interpretation. This form of interpretation is esteemed by Ibn Taimiyah and Ibn Kathir and carries high validity and evidential support. To such an extent, outcomes from the bi al-ma'ṡur interpretation are obligatory and not to be disregarded. This study critically analyzes and validates the bi al-ma’thūr interpretation model that emerged in the mutaqaddimīn era. The focus is on two seminal interpretations, namely "Jāmi' al-Bayān an Ta’wīl Ȃyi al-Qur'ān" by Muhammad bin Jarīr al-Ṭabarī (d. 310 H.) and "Bahr al-‘Ulūm" by Naṣr ibn Muhammad al-Samarqandi (d. 375 H.). This research employs an analytical descriptive approach and falls under library research since primary data source originates from literature within libraries. The research includes verification, used to reevaluate principles and methods of interpretation in relation to contemporary relevance. Findings reveal that despite being considered the best, the bi al-ma’thūr interpretation model exhibits problematic deficiencies. Among these are weak and even questionable authenticity (munkar) in narrations, often with lacking isnads, making distinguishing between reliable (ṣaḥīḥ) and weak (ḍa'īf) challenging. Many narrations include israiliyat (Jewish and Christian narratives) sans commentary or selective narrators, citing negatively-viewed sources. Therefore, interpreting this model is advised to be avoided by audiences lacking expertise in riwayah and dirayah (methods of narration and interpretation).